EVALUATION FOR THE EFFICIENCY OF EARLY SELECTION IN Acacia mangium SEEDLING SEED ORCHARDS BASED ON AGE TRENDS IN GENETIC PARAMETER - Arif Nirsatmanto; Susumu Kurinobu; Susumu Shiraishi (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2012)
The efficiency of early selection was evaluated based on age trend in genetic parameters using tree height data that was measured periodically repeatedly up to age 3 years of age in four seedling seed orchards of Acacia mangium at South Kalimantan, Indonesia. The four orchards were grouped into two populations based upon their provenances, namely: Papua New Guinea (PNG) and Far North Queensland-Australia (FNQ). A model for time trend of genetic parameters was developed by fitting regression equation to the estimates of variances and correlations using tree height data as an independent variable. In both populations, genetic variances and total phenotypic variances increased along with the mean height. Trend of individual heritability along the rotation ages were almost stable at around 0.19 for PNG, and gradually increased from 0.36 to 0.40 for FNQ. Trend of genetic correlations between selection age and rotation age increased rapidly starting at around 0.5 for PNG and 0.6 for FNQ, then exceeding 0.9 at age four years in both populations. Genetic gains due to indirect selection increased with age, in which the gains in FNQ were generally larger than those in PNG. Selection efficiency based on gain per year as a ratio of the gains from indirect selection to direct selection may conclude resulted the optimum age for selection at age two years old in both of PNG and FNQ population.